A kind of hollow tile adhesive and preparation method thereof

By using redispersible latex powder, cellulose ether and other components in ceramic tile glue, combined with epoxy modified acrylic emulsion and other technologies, the bonding problem of low-water absorption tiles under temperature differential stress is solved, which significantly improves the bonding strength and water resistance of ceramic tile glue, and reduces the occurrence of hollowing and shedding problems.

CN119752368APending Publication Date: 2025-04-04GUANGDONG SHUANGHONG WATERPROOF TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411991467.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Existing tiles glue cannot effectively solve the problem of bonding of low-water absorption tiles under temperature differential stress, resulting in the problem of hollowing and falling off in the tiles.

Method used

A hollow tile glue is used, and its formula includes redispersible latex powder, cellulose ether, polyvinyl alcohol, starch ether and crack-resistant fibers. It is used to improve the bonding strength and water resistance through the combination of epoxy modified acrylic emulsion, aqueous tackification emulsion, silane coupling agent and other components.

Benefits of technology

It has achieved the improvement of the bonding strength and water resistance of ceramic tile adhesive, enhanced the bonding effect between ceramic tile and bonding materials, and reduced the occurrence of hollowing and shedding problems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119752368A_ABST
    Figure CN119752368A_ABST
Patent Text Reader

Abstract

The invention discloses a hollow tile adhesive and a preparation method thereof, and relates to the technical field of tile adhesive. The invention comprises redispersible latex powder, cellulose ether, polyvinyl alcohol, starch ether and anti-cracking fiber, wherein the redispersible latex powder, cellulose ether, polyvinyl alcohol, starch ether and anti-cracking fiber are specifically acrylic emulsion, vinyl trimethoxysilane, carbon nanotube, allyl pyrrolidine dithiocarbamate, Tween, N-methyl pyrrolidone, epoxy-modified acrylic emulsion, styrene, acrylamide, and epoxy-modified acrylic emulsion through which deionized water passes, so as to achieve the purpose of rapid demulsification and solidification into film of the product under certain conditions, and at the same time, after the tile adhesive is combined with cement mortar, the active ingredients in the spodumene powder slowly react with cement in water chemistry, and this reaction will cause the strength of the cement mortar to gradually increase, and the addition of polyethylene oxide can greatly increase the direct bonding ability of the tile adhesive with the tile.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of tile back adhesive, in particular to a hollow tile adhesive and a preparation method thereof. Background Art

[0002] With the rapid development of the ceramic tile industry, a large number of large-sized ceramic tiles with low or even zero water absorption have appeared rapidly in recent years, such as ceramic thin plates, vitrified tiles, polished tiles, etc., and tile paving materials have also developed from cement mortar to tile adhesives and tile adhesives. Polished tiles, vitrified tiles and other tiles have low water absorption and smooth and dense bonding surfaces. Traditional paving materials and methods can hardly meet the actual requirements of tile paving. In addition, these tiles are high in strength, sensitive to temperature changes, and have different thermal expansion coefficients from cement. This leads to temperature difference stress after paving larger-sized tiles. Seasonal temperature difference oscillations will destroy the bonding effect between tiles and adhesive materials, resulting in hollowing and falling of tiles.

[0003] Existing tile adhesives mostly use cement mixed with sand and gravel to lay tiles. Cement has high viscosity, but due to the fluctuation of the ratio between water and lime, the bonding strength of cement fluctuates greatly. In addition, since its use requires on-site blending, the work efficiency of personnel is affected.

[0004] Therefore, the existing hollow tile adhesive and its preparation method cannot meet the needs in actual use, so there is an urgent need for improved technology in the market to solve the above problems. Summary of the invention

[0005] The object of the present invention is to provide a hollow tile adhesive and a preparation method thereof, which solves the problems raised in the above-mentioned background technology through the configuration.

[0006] In order to solve the above technical problems, the present invention is achieved through the following technical solutions:

[0007] The present invention discloses a hollow tile adhesive and a preparation method thereof, comprising redispersible latex powder, cellulose ether, polyvinyl alcohol, starch ether and anti-cracking fiber, and is characterized in that the redispersible latex powder, cellulose ether, polyvinyl alcohol, starch ether and anti-cracking fiber are specifically acrylic emulsion, vinyl trimethoxysilane, carbon nanotubes, allyl pyrrolidine dithiocarbamate, Tween, N-methylpyrrolidone, epoxy-modified acrylic emulsion, styrene, acrylamide and deionized water.

[0008] Furthermore, the acrylic emulsion is a multi-polymer emulsion, which includes 5-20% styrene, 10-20% methyl methacrylate, 0.5-5% vinyl acetate, 5-25% methacrylic acid, 0.75-10.6% N-hydroxymethyl acrylamide, 0.1-0.7% potassium persulfate, 0.05-0.8% sodium bisulfite, 0.02-0.98% ferrous sulfate, 8-25% isooctyl acrylate, and 1-15% silicone monomer.

[0009] Furthermore, the epoxy-modified acrylic emulsion comprises 70% water, 30% styrene, 65% butyl acrylate, 5% methacrylic acid, 13% hydroxyethyl acrylate, 12% acrylamide, 18% epoxy resin, 2% nonylphenol polyoxyethylene ether, 1% sodium bicarbonate, 0.75% sodium dodecylsulfobenzenesulfonate, 0.6% ammonium persulfate and 2% curing agent.

[0010] Furthermore, the multi-polymer emulsion is a core-shell structure emulsion, the glass transition temperature of the core layer is 10 to 45°C, the glass transition temperature of the shell layer is -8 to -25°C, and the glass transition temperature of the emulsion is -23 to -1°C.

[0011] Furthermore, the epoxy-modified acrylic emulsion is prepared according to the following steps: 65% of the emulsifier and sodium bicarbonate in a 45°C water bath are emulsified for 8-12 minutes, and then 75% of the acrylic monomer in the formula and the epoxy resin dissolved in isopropanol are added, and the pre-emulsion is emulsified for 50 minutes, and then taken out for use; the remaining emulsifier, acrylic monomer, sodium dodecylthiobenzene sulfonate, and styrene are added to a four-necked bottle, emulsified at 45°C for 15 minutes, and then the temperature is slowly raised to 85°C, and 45% of ammonium persulfate is added to form a seed emulsion; after 25 minutes, the pre-emulsion containing the epoxy resin is dripped, and the dripping is completed in 4 hours, and 35% ammonium persulfate solution is continuously dripped at the same time; after the monomer emulsion is dripped, the reaction system is heated to 90°C and kept warm for 1 hour, during which the remaining ammonium persulfate is added twice; then the reaction system is cooled to 40°C, a curing agent is added, and the pH value is adjusted to 9.0 after continuing to keep warm for 20 minutes, and the material is filtered out.

[0012] A method for preparing hollow tile adhesive comprises the following steps:

[0013] S1: Ingredients: According to the formula requirements, weigh various raw materials in proportion, and then put them into the blender for mixing. The mixing time and speed should be controlled to ensure uniform mixing;

[0014] S2: Mixing: Put the stirred ingredients into the mixer for mixing. The mixing temperature and time should also be controlled to ensure uniform mixing;

[0015] S3: Grinding: Put the mixed materials into the grinder for grinding. The fineness and uniformity of grinding should be well controlled to avoid uneven particle sizes.

[0016] S4: Color adjustment: If you need to produce tile adhesives of different colors, you can adjust the colors in this step. The proportion and color of the color adjustment must meet the requirements;

[0017] S5: Packaging: Put the ground and colored tile adhesive into the packaging bag for packaging. The quality and sealing of the packaging bag must be well controlled to avoid air leakage or material leakage.

[0018] Furthermore, in S1, the epoxy-modified acrylic emulsion, the aqueous tackifying emulsion, the demulsifier, the coupling agent, the defoaming agent, the film-forming aid and the mildew-proof agent are physically mixed to obtain a water-resistant one-component tile adhesive.

[0019] Further, the aqueous tackifying emulsion is a rosin emulsion, and the main component is a rosin modified resin. Further, when preparing the hollow tile adhesive, the following points need to be noted:

[0020] (1) Select appropriate raw materials: Select appropriate raw materials according to the requirements of hollow tile adhesive to ensure that the performance and quality of the adhesive meet the requirements;

[0021] (2) Control the production process: During the preparation process, various process parameters must be controlled, such as stirring time, mixing temperature, grinding fineness, etc., to ensure the stable quality of the produced tile adhesive;

[0022] (3) Adjust the formula: According to different application scenarios and tile types, the formula of tile adhesive can be appropriately adjusted to obtain better bonding effect;

[0023] (4) Storage and transportation: The prepared tile adhesive should be stored in a dry, cool place, away from moisture and direct sunlight. Avoid collision and extrusion during transportation to avoid affecting product quality.

[0024] Furthermore, firstly, the tile adhesive is evenly applied to the back of the tile, and the amount of tile adhesive used for each square tile is 1 kg; then cement mortar is prepared according to the ratio of cement: sand = 1:1, and the cement mortar prepared in this ratio is used to paste the tiles.

[0025] The present invention has the following beneficial effects:

[0026] The epoxy-modified acrylic emulsion of the present invention is matched with an aqueous tackifying emulsion and a silane coupling agent to achieve the purpose of improving the bonding strength and water resistance of the product, and by adding a certain amount of demulsifier and film-forming aid, the purpose of rapid demulsification and solidification of the product under certain conditions is achieved. At the same time, after the tile adhesive is combined with the cement mortar, the active ingredients in the spodumene powder slowly react with the cement in a water chemical reaction, and this reaction will cause the strength of the cement mortar to gradually increase, and the addition of polyethylene oxide can greatly increase the direct bonding ability between the tile adhesive and the tile.

[0027] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0029] Figure 1 The figure is a schematic diagram of the preparation process of the tile adhesive of the present invention. DETAILED DESCRIPTION

[0030] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings in the embodiments of the present invention.

[0031] Example 1

[0032] See also Figure 1 As shown, this embodiment is a hollow tile adhesive and a preparation method thereof, including redispersible latex powder, cellulose ether, polyvinyl alcohol, starch ether and anti-cracking fiber, wherein the redispersible latex powder, cellulose ether, polyvinyl alcohol, starch ether and anti-cracking fiber are specifically acrylic emulsion, vinyltrimethoxysilane, carbon nanotubes, allyl pyrrolidine dithiocarbamate, Tween, N-methylpyrrolidone, epoxy-modified acrylic emulsion, styrene, acrylamide and deionized water.

[0033] Preferably, the acrylic emulsion is a multi-polymer emulsion, which includes 5-20% styrene, 10-20% methyl methacrylate, 0.5-5% vinyl acetate, 5-25% methacrylic acid, 0.75-10.6% N-hydroxymethyl acrylamide, 0.1-0.7% potassium persulfate, 0.05-0.8% sodium bisulfite, 0.02-0.98% ferrous sulfate, 8-25% isooctyl acrylate, and 1-15% silicone monomer.

[0034] Preferably, the epoxy-modified acrylic emulsion comprises 70% water, 30% styrene, 65% butyl acrylate, 5% methacrylic acid, 13% hydroxyethyl acrylate, 12% acrylamide, 18% epoxy resin, 2% nonylphenol polyoxyethylene ether, 1% sodium bicarbonate, 0.75% sodium dodecylsulfobenzenesulfonate, 0.6% ammonium persulfate and 2% curing agent.

[0035] Preferably, the multi-polymer emulsion is a core-shell structure emulsion, the glass transition temperature of the core layer is 10 to 45°C, the glass transition temperature of the shell layer is -8 to -25°C, and the glass transition temperature of the emulsion is -23 to -1°C.

[0036] Preferably, the epoxy-modified acrylic emulsion is prepared according to the following steps: 65% of the emulsifier and sodium bicarbonate in a 45°C water bath are emulsified for 8-12 minutes, then 75% of the acrylic monomer in the formula and all the epoxy resin dissolved in isopropanol are added, emulsified for 50 minutes to obtain a pre-emulsion, which is taken out for use; the remaining emulsifier, acrylic monomer, sodium dodecylthiobenzene sulfonate and styrene are added to a four-necked bottle, emulsified at 45°C for 15 minutes, then slowly heated to 85°C, and 45% ammonium persulfate is added to form a seed emulsion; after 25 minutes, the pre-emulsion containing the epoxy resin is dripped, and the dripping is completed in 4 hours, while 35% ammonium persulfate solution is continuously dripped; after the monomer emulsion is dripped, the reaction system is heated to 90°C and kept warm for 1 hour, during which the remaining ammonium persulfate is added twice; then the reaction system is cooled to 40°C, a curing agent is added, and the pH value is adjusted to 9.0 after continuing to keep warm for 20 minutes, and the material is filtered out.

[0037] A method for preparing hollow tile adhesive, characterized in that it comprises the following steps;

[0038] S1: Ingredients: According to the formula requirements, weigh various raw materials according to the proportion, and then put them into the blender for mixing. The mixing time and speed should be controlled to ensure uniform mixing;

[0039] S2: Mixing: Put the stirred ingredients into the mixer for mixing. The mixing temperature and time should also be controlled to ensure uniform mixing;

[0040] S3: Grinding: Put the mixed materials into the grinder for grinding. The fineness and uniformity of grinding should be well controlled to avoid uneven particle sizes.

[0041] S4: Color adjustment: If you need to produce tile adhesives of different colors, you can adjust the colors in this step. The proportion and color of the color adjustment must meet the requirements;

[0042] S5: Packaging: Put the ground and colored tile adhesive into the packaging bag for packaging. The quality and sealing of the packaging bag must be well controlled to avoid air leakage or material leakage.

[0043] Preferably, in S1, epoxy-modified acrylic emulsion, aqueous tackifying emulsion, demulsifier, coupling agent, defoamer, film-forming aid and mildew-proof agent are physically mixed to obtain water-resistant one-component tile adhesive.

[0044] Preferably, the aqueous tackifying emulsion is a rosin emulsion, the main component of which is a rosin modified resin.

[0045] Preferably, when preparing hollow tile adhesive, the following points need to be noted:

[0046] (1) Select appropriate raw materials: Select appropriate raw materials according to the requirements of hollow tile adhesive to ensure that the performance and quality of the adhesive meet the requirements;

[0047] (2) Control the production process: During the preparation process, various process parameters must be controlled, such as stirring time, mixing temperature, grinding fineness, etc., to ensure the stable quality of the produced tile adhesive;

[0048] (3) Adjust the formula: According to different application scenarios and tile types, the formula of tile adhesive can be appropriately adjusted to obtain better bonding effect;

[0049] (4) Storage and transportation: The prepared tile adhesive should be stored in a dry, cool place, away from moisture and direct sunlight. Avoid collision and extrusion during transportation to avoid affecting product quality.

[0050] Preferably, the tile adhesive is first evenly applied to the back of the tile, with the amount of tile adhesive used for each square of tile being 1 kg; then cement mortar is prepared in a ratio of cement: sand = 1:1, and the cement mortar prepared in this ratio is used to paste the tiles.

[0051] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0052] In the description of the present invention, it is also necessary to explain that, unless otherwise clearly specified and limited, the terms "set", "install", "connect", and "connect" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two elements. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0053] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A hollow tile adhesive, comprising redispersible latex powder, cellulose ether, polyvinyl alcohol, starch ether and anti-cracking fiber, characterized in that; The redispersible latex powder, cellulose ether, polyvinyl alcohol, starch ether and anti-cracking fiber are specifically acrylic emulsion, vinyl trimethoxysilane, carbon nanotubes, allyl pyrrolidine dithiocarbamate, Tween, N-methylpyrrolidone, epoxy-modified acrylic emulsion, styrene, acrylamide and deionized water.

2. The hollow tile adhesive according to claim 1, characterized in that: The acrylic emulsion is a multi-polymer emulsion, which includes 5-20% styrene, 10-20% methyl methacrylate, 0.5-5% vinyl acetate, 5-25% methacrylic acid, 0.75-10.6% N-hydroxymethyl acrylamide, 0.1-0.7% potassium persulfate, 0.05-0.8% sodium bisulfite, 0.02-0.98% ferrous sulfate, 8-25% isooctyl acrylate, and 1-15% silicone monomer.

3. The hollow tile adhesive according to claim 1, characterized in that: The epoxy modified acrylic emulsion comprises 70% water, 30% styrene, 65% butyl acrylate, 5% methacrylic acid, 13% hydroxyethyl acrylate, 12% acrylamide, 18% epoxy resin, 2% nonylphenol polyoxyethylene ether, 1% sodium bicarbonate, 0.75% sodium dodecylthiobenzene sulfonate, 0.6% ammonium persulfate and 2% curing agent.

4. The hollow tile adhesive according to claim 1, characterized in that: The multi-component copolymer latex is a core-shell structure latex, the glass transition temperature of the core layer is 10-45°C, the glass transition temperature of the shell layer is -8--25°C, and the glass transition temperature of the latex is -23--1°C.

5. The hollow tile adhesive according to claim 3, characterized in that: The epoxy modified acrylic emulsion is prepared according to the following steps: 65% of the emulsifier and sodium bicarbonate in a 45°C water bath are placed for emulsification for 8-12 minutes, then 75% of the acrylic monomer in the formula and the epoxy resin dissolved in isopropanol are added, emulsified for 50 minutes to obtain a pre-emulsion, which is taken out for use; the remaining emulsifier, acrylic monomer, sodium dodecylthiobenzene sulfonate and styrene are added to a four-necked bottle, emulsified at 45°C for 15 minutes, then the temperature is slowly raised to 85°C, 45% of ammonium persulfate is added to form a seed emulsion; after 25 minutes, the pre-emulsion containing the epoxy resin is dripped, and the dripping is completed in 4 hours, and 35% of ammonium persulfate solution is continuously dripped at the same time; after the monomer emulsion is dripped, the reaction system is heated to 90°C and kept warm for 1 hour, during which the remaining ammonium persulfate is added twice; then the reaction system is cooled to 40°C, a curing agent is added, the temperature is continuously kept warm for 20 minutes, the pH value is adjusted to 9.0, and the material is filtered out.

6. A method for preparing hollow tile adhesive according to claims 1-5, characterized in that ,, including the following steps; S1: Ingredients: According to the formula requirements, weigh various raw materials in proportion, and then put them into the blender for mixing. The mixing time and speed should be controlled to ensure uniform mixing; S2: Mixing: Put the stirred ingredients into the mixer for mixing. The mixing temperature and time should also be controlled to ensure uniform mixing; S3: Grinding: Put the mixed materials into the grinder for grinding. The fineness and uniformity of grinding should be well controlled to avoid uneven particle sizes. S4: Color adjustment: If you need to produce tile adhesives of different colors, you can adjust the colors in this step. The proportion and color of the color adjustment must meet the requirements; S5: Packaging: Put the ground and colored tile adhesive into the packaging bag for packaging. The quality and sealing of the packaging bag must be well controlled to avoid air leakage or material leakage.

7. The method for preparing hollow tile adhesive according to claim 6, characterized in that: In the S1, epoxy-modified acrylic emulsion, aqueous tackifying emulsion, demulsifier, coupling agent, defoamer, film-forming aid and mildew-proof agent are physically mixed to obtain a water-resistant single-component tile adhesive.

8. The method for preparing hollow tile adhesive according to claim 7, characterized in that: The aqueous tackifying emulsion is a rosin emulsion, the main component of which is a rosin modified resin.

9. The method for preparing hollow tile adhesive according to claim 6, characterized in that: When preparing hollow tile adhesive, the following points should be noted: (1) Select appropriate raw materials: Select appropriate raw materials according to the requirements of hollow tile adhesive to ensure that the performance and quality of the adhesive meet the requirements; (2) Control the production process: During the preparation process, various process parameters must be controlled, such as stirring time, mixing temperature, grinding fineness, etc., to ensure the stable quality of the produced tile adhesive; (3) Adjust the formula: According to different application scenarios and tile types, the formula of tile adhesive can be appropriately adjusted to obtain better bonding effect; (4) Storage and transportation: The prepared tile adhesive should be stored in a dry, cool place, away from moisture and direct sunlight. Avoid collision and extrusion during transportation to avoid affecting product quality.

10. The method for preparing hollow tile adhesive according to claim 16, characterized in that: First, the tile adhesive is evenly applied to the back of the tile, and the amount of tile adhesive used for each square tile is 1 kg; then cement mortar is prepared according to the ratio of cement: sand = 1:1, and the cement mortar prepared in this ratio is used to paste the tiles.